Frequency and Pattern of GIT Anomalies in Neonates: A Retrospective Study at NICU Mayo Hospital Lahore - Muhammad Kashif Bashir, Jamshaid Javed, Rubab Ameer, Rida Ajmal Khan, Hamna Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To acknowledge magnitude and spectrum of congenital anomalies of gastrointestinal tract in neonates and to establish possible factors resulting in these congenital anomalies. Material And Methods: The design of this study was Retrospective observational study. This study was conducted at NICU department of pediatric surgery King Edward medical university / Mayo hospital Lahore from June 2021 to May 2022. Neonates admitted in NICU department of pediatric surgery with gastrointestinal congenital anomaly were included in this study. Neonates having congenital anomaly other than GIT were excluded. Patient information regarding diagnosis and possible cause of congenital anomaly was noted on prescribed proforma. Results: During the study period total 256 neonates were admitted in neonatal ICU department of pediatric surgery Mayo hospital Lahore. Out of these 156(60.9%) neonates were having congenital anomalies of gastrointestinal tract while reaming 100(39.1%) neonates were having congenital anomalies of other structures. Most common congenital anomaly of GIT was anorectal malformations 35(22.4%) followed by Intestinal atresia’s in 30(19.2%). Conclusion: Congenital anomalies play an important role in neonatal mortality rate of any developing country like Pakistan. Chromosomal disorders, environmental and infectious factors are major contributing factors. Gastrointestinal tract anomalies are the most common anomalies of neonates with predominance of anorectal malformations. Antenatal care and timely interventions can reduce frequency of these anomalies.